A semi-empirical model of boreal-forest gross primary production, evapotranspiration, and soil water - calibration and sensitivity analysis - Peltoniemi, Mikko; Pulkkinen, Minna; Aurela, Mika; Pumpanen, Jukka; Kolari, Pasi; Mäkelä, Annikki
2015